Impact of Mono- and Dual-Sized α-Fe2O3 Catalyst Mixtures on the Thermochemical Processing of Pinewood for Upgraded Liquid Chemicals - Baimoldina, Adel; Papadikis, Konstantinos; Konysheva, Elena Yu. (Frontiers in Energy Research, 2022)
The incorporation of mono-sized particle catalysts in real industrial systems for biomass conversion is a significant challenge, hence the impact of individual α-Fe2O3 catalysts with varying non-ideal spherical sizes of 54 nm (FS054), 221 nm (FS221), and ∼2 µm (FSm002) as well as dual-sized mixtures (FS054-FS221 and FS221-FSm002) were considered in the catalytic upgrading of pinewood pyrolysis vapors. The size variation of the α-Fe2O3 catalyst revealed a substantial effect on the product distribution. Although the yield of phenols shows a decrease by almost a factor of two irrespective of the catalyst particle size, the FS221 catalyst demonstrates the most potent effect on reducing phenols through decarboxylation reactions. Considering the role of the catalyst on the individual phenolics, the FS221 catalyst reveals higher selectivity towards the reduction of 2-methoxyphenol, isoeugenol, and eugenol, whereas the application of FS054 catalysts displays a stronger impact on the decrease of creosol and other phenols. Both FS054 and FS221 catalysts showed the highest effectiveness in reducing the relative yield of 2-methoxy-4-vinylphenol. Applying a dual-size mixture (FS054-FS221) shows a synergetic effect, simultaneously decreasing the content of phenols, acids, and aldehydes followed by a strong CO2 release attributed to competitive decarbonylation reactions of aldehydes. The appearance of γ-Fe2O3 small fraction was revealed in the powders with mono-(FS221) and dual particle size (FS054-FS221 and FS221-FSm002), whereas the FS054 and FSm002 catalysts demonstrate good chemical and phase stability.